Bloodless treatment of residual bile duct stones - Mazzarielo, Rodolfo (Cirugía del Uruguay, 1975)
In an 11-year period, 570 patients witll residual calculi of the biliary tract were treated with the nonsurgical method. In 543 if these patients, that is, in 95.3 % of he cases, instrumental removal of the calculi was achieved. These figures include trans-cystic and transcholecystic extractions. The high percentage of succeses, the very low morbility and the satisfactory results in the follow-up make this resource definitively useful, to be taken into consideration together with other treatments of the biliary pathology.